THE ALLEVIATION OF SALT STRESS BY THE ACTIVITY OF AM FUNGI IN GROWTH AND PRODUCTIVITY OF ONION (ALLIUM CEPA L.) PLANT: Life Science-Botany - SHINDE S.K.; SHINDE BP; PATALE SW (International Journal of Life Science and Pharma Research, 2013)
AM fungi are balanced mutuailistc association in which the fungus and plant exchange commodities required for growth & survival. AMF have been shown to promote plant growth &nutrient uptake and are particularly important for phosphorus nutrition. We hypothesize the experiments in the present study that AMF reduces salt stress in plant. To prove this we conducted experiments to determine the benefits of mycorrhizal fungi by comparing mycorrhizal fungal inoculated Onion plants to non inoculated plants under different salt concentration in the soil .salinity affects the plant growth with increasing stress rate at higher salt concentration particular in non inoculated plants. AMF containing onion plants were healthier than non mycorrhizal Onion plant. Inoculated plants were healthier than at low salt concentration however higher salt concentration affects the growth. The fresh and dry biomass is more in AMF inoculated plant than non inoculated. The mycorrhizal inoculated plants in salt concentration had higher root mass colonization compared to high salt concentration.